Bahasa Inggris - Prisna Dea Leonita; Ahmad Izzuddin; Jekti Rahayu (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2025)
The rapid development of technology that provides online shopping system facilities has changed the way consumers behave in shopping. Nowadays consumers prefer to shop online rather than offline, because consumers do not need to leave the house to see the appearance of the product and buy the product. This study aims to find out and analyze the influence of Live Streaming, influencer marketing and price discounts on impulse purchases at tiktok shops in Jember Regency. This type of research uses a quantitative method with a sample of 130 respondents and uses the Non Probability Sampling Technique with a purposive sampling approach with the help of questionnaires as the main tool in collecting respondent data. The data analysis technique of this study uses instrument testing, classical assumptions, multiple linear regression, hypotheses and determination coefficients. The results of the analysis obtained showed that Live Streaming, influencer marketing and price discounts partially had a positive and significant effect on impulse purchases, with a contribution rate of 63%.